The inhibitory effect of Isoflavones isolated from Caesalpinia pulcherrima on aldose reductase in STZ induced diabetic rats. (25th July 2015) - Kumar, Munipally Praveen; Sankeshi, Venu; Naik, R. Ravindar; Thirupathi, P.; Das, Biswanath; Raju, T.N.
Highlights: Protective role of Isoflavones in STZ induced diabetic rats was studied. Supplementation of Isoflavones was found to alter oxidative stress markers. 3, 6, 7, 4′, 5′-Pentamethoxy-5, 3′-dihydroxyflavone exhibited non-competitive inhibition against AR. Ability to inhibit AR and delaying of DR by Isoflavones has been revealed. Abstract: Increased aldose reductase activity has been implicated in the development of retinopathy due to accumulation of intracellular sugar alcohol, i.e., sorbitol. In this study, the compounds isolated from the Caesalpinia pulcherrima, have been examined for its inhibitory effects on aldose reductase (AR), which plays a major role in diabetic retinopathy. 3, 6, 7, 4′, 5′-Pentamethoxy-5, 3′-dihydroxyflavone (Compound 2 ) has shown significant inhibition of rat retina AR with an IC50 value of 16.24 ± 0.046 μM in a non-competitive manner. Molecular docking study results are steady with the pattern of AR inhibition by Compound 2 and its specificity. The supplementation of Compound 2 suppresses sorbitol accumulation in retina by decreased AR activity in STZ induced diabetic rat in dose dependent manner. Besides this, rats fed with Compound 2 have shown improved levels of antioxidant enzymes. This study revealed that Compound 2 has pharmacologically active component with a potential to inhibit rat retina AR and affecting the delaying process of diabetic retinopathy in STZ induced diabetic rats.